Core-pulling prevention winding needle - XIE SILIANG; DAI JIANYONG (2022)
An anti-core-pulling winding needle comprises a base and two needle rods installed on the base in a spaced mode, a limiting rail is arranged on the base, an ejector rod, a sliding block and two springs are arranged in the limiting rail, the ejector rod is arranged towards the position between the two needle rods in a spaced mode, the two springs are located at the two ends of the limiting rail respectively, and each spring abuts against the corresponding needle rod; each needle rod is provided with a clamping piece, the two clamping pieces are connected with the sliding block, the clamping pieces on the needle rods can clamp a pole piece when getting close to each other, and when the ejector rod retracts, the spring can drive the two needle rods to get close to each other, so that the innermost ring of the winding core is partially separated from the needle rods, the contact area between the winding needle and the winding core is reduced, and the resistance when the winding needle is pulled out is reduced; th